TEKNIK ASSERTIVE TRAINING (AT) UNTUK MENINGKATKAN PERILAKU ASERTIF SISWA - Nurfaizal, author (JURNAL FOKUS KONSELING, 2015)
This study was conducted based on the problem of low assertive behavior skill. Assertive is a behavior in which person are able to act upon desire. Held the right and not utilized by others. Besides that , going to be assertive means communicating what is expected clearly by respecting personality right and other right. The purpose of the study is to gain the description of effectiveness assertive training technique for improving studentsâ assertive behavior. This study used quasi-experimental method with non equivalent control group design. The population was students of senior high school Kartika Siliwangi 2 Bandung in academic years 2012/2013. Purposive sampling technique was employed for taking the sample. The result of the study showed that (1) 40,7% studentsâ assertive behavior profile was in the assertive category and 59,3% was not; (2) assertive training technique was effective to improve studentsâ assertive behavior; (3) there was no the difference of assertive behavior between male and female students.Keywords: assertive training, assertive behavior.